Meningkatkan Karakteristik Peserta Didik Tentang Pergaulan Bebas Melalui Metode Example Non Examples - Hasanah, Dewi (Jurnal Ilmiah Bina Manajemen, 2019)
This study aims to improve students' knowledge about promiscuity, this research includes classroom action research consisting of two experiments with learning methods that contain examples not examples. In the first cycle the percentage of completeness reached 47.82%, while the second cycle reached 86.96%. Improvement of student learning outcomes in free promiscuity material using short examples, not examples from cycle I to cycle II amounted to 39.13%. Based on these results, the study can conclude that the sample method is not an example that can be used as a special learning method in the delivery of free promiscuity in the hope that even fewer children are not involved in promiscuity